Suatu Tinjauan Penyebab Kepindahan Dosen Perguruan Tinggi Negeri (PTN) ke Luar Negeri - Idi Setyo Utomo (Bina Nusantara University, 2004)
Article discusses lecturers plan to teach abroad. This article explains the main reason of working satisfaction, those are money, working safety, schedule, and envolvement in working environment. For the last three main reasons, which are working safety, schedule, and envolvement in working environment, the lecturers generally satisfied. The main reason that is assumed to have a big influence in lecturer plan to teach abroad is bigger salary (money).